PENGARUH MEDIA ALPHABET MACHINE TERHADAP KEMAMPUAN MEMBACA PEMULAAN ANAK DI TAMAN KANAK-KANAK NEGERI 1 PADANG - Naila Amelia; Tisna Syafnita; Elise Muryanti (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study is motivated by the importance of stimulating early reading skills in early childhood as the foundation for recognizing letters, sounds, and simple word meanings. Early reading ability needs to be developed through the use of learning media that is attractive, varied, and appropriate to the learning characteristics of young children. This study aims to determine the effect of Alphabet Machine media on early reading skills of children at TK Negeri 1 Padang. This study used a quantitative approach with a quasi-experimental design. The research sample consisted of two classes, namely class B2 as the experimental class and class B4 as the control class, each consisting of 15 children. The experimental class received treatment using Alphabet Machine media, while the control class used conventional picture media. Data were collected through pre-test and post-test instruments and analyzed using normality tests, homogeneity tests, and hypothesis testing with Independent Samples T-Test using SPSS Version 27. The results showed that the average pre-test score of the experimental class was 12.8 and increased to 19.8 in the post-test, while the control class increased from an average of 12.4 to 15.93. Based on hypothesis testing, the Sig. (2-tailed) value was <0.001, which is less than 0.05, meaning Ha is accepted and Ho is rejected. It can be concluded that there is a significant effect of Alphabet Machine media on early reading skills of children at TK Negeri 1 Padang.